Defect States Determining Dynamic Trapping-Detrapping in β-Ga2O3 Field-Effect Transistors. (16th January 2019) - Polyakov, Alexander Y.; Smirnov, Nikolai B.; Shchemerov, Ivan V.; Chernykh, Sergey V.; Oh, Sooyeoun; Pearton, Stephen J.; Ren, Fan; Kochkova, Anastasia; Kim, Jihyun
Abstract : β-Ga2 O3 is an intriguing material as a channel layer for the next generation high power transistors. To assess the device level effects of the traps in β-Ga2 O3, the dynamic dispersion characteristics of a back-gated nanobelt β-Ga2 O3 field-effect transistor prepared by mechanical exfoliation from a bulk β-Ga2 O3 single crystal was investigated by the dependence of threshold voltage hysteresis on transistor transfer characteristics on the gate voltage ramp, pulsed current-voltage characteristics, and current deep level transient spectroscopy measurements. Current lag in the off-state was related to the presence of electron traps at Ec -0.75 eV, which are also present in bulk crystals and ascribed to Fe impurities or native defects. In the on-state, drain current lag was caused by surface traps with levels at Ec -(0.95–1.1) eV. Optimized passivation layers for β-Ga2 O3 are required to prevent the current collapse because the device performances are affected by the environmental molecules adsorbed on the surface. Our work can pave a way to mitigating the defect-related current collapse in β-Ga2 O3 electronic devices.